PEMANFAATAN BAHAN LOKAL BAMBU MAYAN SEBAGAI BAHAN SUBSTITUSI ANGREGAT PADA BETON - Mulyati, Ely (Universitas Bina Taruna Gorontalo, 2023)
Bamboo is a plant that can be found around us, especially in rural areas. Bamboo is an environmentally friendly building material compared to conventional building materials. In addition to being easily accessible, cheap, and lightweight, bamboo also possesses considerable strength. There have been numerous studies on the use of bamboo, but in this research, bamboo is utilized as a substitute material for coarse aggregates. The planned compressive strength is for concrete with a compressive strength of K250 (20.75MPa) with substitution proportions of 30%, 50%, and 100%, which will be compared with normal concrete. In this study, it is expected to determine the proportion of substitution of coarse aggregates in concrete using bamboo. Based on the tests conducted, ranging from testing concrete-forming materials to compressive strength tests, the compressive strength obtained for normal concrete (0%) at 28 days is 26 MPa. Meanwhile, the compressive strength for concrete with a 30% substitution proportion is 26 MPa, 50% proportion is 13 MPa, and 100% proportion is 9 MPa. Thus, it can be concluded that the greater the percentage of concrete substitution, the lower the compressive strength obtained.